Perancangan Sistem Deteksi Warna Real-Time Menggunakan Metode Gaussian Blur Dan Ruang Warna HSV - Nur Rochim, Ferdi; Desky Sompie, Grivi; Mua’mmar; Imam Saputra, Rizky; Rosyani, Perani (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Color detection is a crucial process in recognizing objects based on their color characteristics in an image. This research designs a real-time color detection system using OpenCV and HSV color space to aid individuals in easily identifying colors. The system employs image processing techniques such as Gaussian blur and morphological operations to enhance detection accuracy. Designed to detect and recognize multiple colors including red, green, blue, yellow, orange, purple, brown, black, white, and gray, the system displays detection results by drawing bounding boxes around detected objects and providing clear and readable color labels. Implemented by accessing the camera directly, processing each frame in real-time, and displaying detection results on-screen, the system demonstrates satisfactory performance in good lighting conditions and is capable of detecting objects of various sizes, thereby providing significant visual assistance in color identification and differentiation in the surrounding environment.